Modeling, simulation and optimization of 14nm high-K/metal gate NMOS with taguchi method - Mah S.K.; Ahmad I.; Ker P.J.; Tan K.P.; Faizah Z.A.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Analysis of variance (ANOVA); Electron beam lithography; Metals; MOS devices; Oxide semiconductors; Taguchi methods; ATHENA; ATLAS; Electrical characteristic; Electronics technology; International Technology Roadmap for Semiconductors; MOS-FET; Simulation and optimization; Taguchi optimization method; MOSFET devices